Adaptation of Educational Programs in Uzbekistan to the Requirements of the Digital Economy - pcadmin, Ravshan Rakhimovich KHUSAINOV (Global Scientific Publishing, 2025)
In Uzbekistan, it is necessary to adapt educational programs to the requirements of the digital economy. This is an important step towards increasing the country's competitiveness in the global market. The article discusses the current state of training specialists in the field of information technology and the impact of digital transformation on the education system. Examples of the implementation of new educational standards and technologies are also presented. However, when adjusting programs, educational institutions face a number of problems. The article discusses these problems and possible solutions
Keywords: digital economy; educational programs